Penerapan Teknologi Terpadu Pro-Organik Pada Budidaya Tanaman Padi di Kecamatan Jetis Kabupaten Ponorogo - Navitasari, Lisa; Suhirmanto, Suhirmanto (LPPM Universitas Trunojoyo Madura, 2025)
Fertilizer is a substance that provides nutrients for plants. Deficiency of fertilizer results in stunted plant growth and development. Therefore with the condition of the scarcity of chemical fertilizers that occurs in Indonesia decrease of productivity. This is impact in the government's efforts to promote the pro-organic movement. One of the pro-organic movement is learning through field schools (SL) about integrated pro-organic technology in rice cultivation. Integrated pro-organic technology thaat includes the use of organic fertilizer, biological agents/local microorganisms, botanical pesticides and biosaka. This SL activity is carried out as a form of community service in overcoming the problem of scarcity and farmers' dependence on chemical fertilizers. Besides that, integrated pro-organic technology is also expected to be able to maintain the stability of rice plant productivity. The aim of this community service is to maintain the productivity of rice plants with integrated pro-organic technology. This activity was implemented in 10 farmer groups in Jetis District, Ponorogo Regency. The method used is learning and practice through field schools about integrated pro-organic technology which includes organic fertilizer, biological agents/local microorganisms, vegetable pesticides, and Biosaka. Furthermore, rice cultivation using integrated pro-organic technology in 10 farmer groups. The results of the application of integrated pro organic technology showed that integrated pro organic technology is able to maintain and increase the productivity of rice plants by 7.49 tonnes/ha compared to rice cultivation without pro organic technology of 7.22 tonnes/ha. These results increase the enthusiasm of farmer groups in carrying out pro-organic cultivation in the midst of a scarcity of fertilizer